Phytochemical Analysis of Some Indigenous Plants Potent Against Endoparasite - Prashant Yadav (Journal of Advanced Laboratory Research in Biology, 2010)
A study has been done with indigenous plants to explore their phytochemical constituents. About 7 indigenous plants collected from Agra–Mathura Region. The collected plants undergone extraction followed by evaporation. The prepared plant extract goes through phytochemical investigation to explore active constituents which are very significant drug development.